Project Planning as an aspect of successful completion of Donor Funded Water Projects in Baringo County, Kenya. - DENIS OUMA; Kutol Cherutich (Cita konsultindo, 2026)
Water is an essential resource for human survival and economic growth, yet access to clean and safe water remains a significant challenge with limited literature review aligned to semi-arid regions. This study focused on the influence Project Planning in the successful completion of donor-funded water projects in Baringo County where many initiatives and struggles to meet water project success is a mirage despite substantial investment. The study was anchored on the theory of planning and the theory of execution. The study employed a descriptive research design and gathered data from 357 stakeholders across various donor-funded water initiatives through a structured questionnaire. The sample size used of 84 respondents included project managers, staff, donor representatives, community members, and government officials. The study found that Project Planning, significantly affected successful completion of donor-funded water projects in Baringo County. The findings show that to improve project outcomes, it is vital to establish more consistent and comprehensive planning practices with clearer definition and communication of project scopes. Adherence to timelines and better resource allocation needed to be emphasized. Project teams were to ensure that contingency plans are not only developed but regularly updated and integrated into daily management. Strengthening of planning frameworks could help reduce schedule slippages and budget overruns, thereby increasing the likelihood of timely and successful project completion.